The tarsal-metatarsal complex of caviomorph rodents: Anatomy and functional-adaptive analysis - Candela, Adriana Magdalena (2017)
Caviomorph rodents represent a major adaptive radiation of Neotropical mammals. They occupy a variety of ecological niches, which is also reflected in their wide array of locomotor behaviors. It is expected that this radiation would be mirrored by an equivalent disparity of tarsal-metatarsal morphology. Here, the tarsal-metatarsal complex of Erethizontidae, Cuniculidae, Dasyproctidae, Caviidae, Chinchillidae, Octodontidae, Ctenomyidae, and Echimyidae was examined, in order to evaluate its anatomical variation and functional-adaptive relevance in relation to locomotor behaviors. A qualitative study in functional morphology and a geometric morphometric analysis were performed. We recognized two distinct tarsal-metatarsal patterns that represent the extremes of anatomical variation in the foot. The first, typically present in arboreal species, is characterized by features that facilitate movements at different levels of the tarsal-metatarsal complex. The second pattern, typically present in cursorial caviomorphs, has a set of features that act to stabilize the joints, improve the interlocking of the tarsal bones, and restrict movements to the parasagittal plane. The morphological disparity recognized in this study seems to result from specific locomotor adaptations to climb, dig, run, jump and swim, as well as phylogenetic effects within and among the groups studies.